1995
DOI: 10.1016/0092-8674(95)90073-x
|View full text |Cite
|
Sign up to set email alerts
|

β-amyloid precursor protein-deficient mice show reactive gliosis and decreased locomotor activity

Abstract: In several pedigrees of early onset familial Alzheimer's disease (FAD), point mutations in the beta-amyloid precursor protein (APP) gene are genetically linked to the disease. This finding implicates APP in the pathogenesis of Alzheimer's disease in these individuals. To understand the in vivo function of APP and its processing, we have generated an APP-null mutation in mice. Homozygous APP-deficient mice were viable and fertile. However, the mutant animals weighed 15%-20% less than age-matched wild-type contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
435
1
8

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(470 citation statements)
references
References 45 publications
24
435
1
8
Order By: Relevance
“…Two specifically immunoreactive AICD proteins, a major band of Ϸ5 kDa and a minor band of Ϸ7 kDa, were routinely detected in freshly prepared brain homogenates with either antibody. Both these proteins were absent in the brains of mice lacking APP expression (40) and increased in the brains of transgenic mice overexpressing human APP (41) (Fig. 2A).…”
Section: Decreased A␤ Catabolism and In Vivo Accumulation Of A␤ In Idmentioning
confidence: 97%
See 2 more Smart Citations
“…Two specifically immunoreactive AICD proteins, a major band of Ϸ5 kDa and a minor band of Ϸ7 kDa, were routinely detected in freshly prepared brain homogenates with either antibody. Both these proteins were absent in the brains of mice lacking APP expression (40) and increased in the brains of transgenic mice overexpressing human APP (41) (Fig. 2A).…”
Section: Decreased A␤ Catabolism and In Vivo Accumulation Of A␤ In Idmentioning
confidence: 97%
“…To characterize the role of IDE in A␤ metabolism in brain, the principal site of A␤ accumulation, we compared degradation of 100 pM 125 I-A␤ 40 in both soluble and Na 2 CO 3 -washed membrane fractions of brain from WT and IDE Ϫ͞Ϫ mice. TCA precipitation assays (see Materials and Methods) were performed at reaction times 0, 3, and 8 h for membranes and at 0, 30, and 60 min for soluble fractions.…”
Section: Decreased A␤ Catabolism and In Vivo Accumulation Of A␤ In Idmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of the APP gene in mice resulted in neither early mortality, nor appreciable morbidity, although these mice exhibited reactive gliosis and changes in locomotor behavior [154]. The lack of vital consequence of APP deletion in vivo may result from the fact that mammals express proteins closely homologous to APP, the APP-like proteins (APLPs) [155].…”
Section: Transgenic Mouse Models For Eoadmentioning
confidence: 99%
“…A mouse model that is deficient in ␤PP has been developed and exhibits phenotypic abnormalities including: reactive gliosis, a reduced forelimb grip strength, and decreased locomotion. 3 While the reasons underlying the phenotypic changes in the ␤PP-deficient mice have not been thoroughly explored, the model does argue that ␤PP is important for normal nervous system function. We began our investigations to determine the biology of neuronal ␤PP and have recently shown that ␤PP contributes to neuronal viability and neuron differentiation in vitro.…”
mentioning
confidence: 99%